2017
DOI: 10.1515/folmed-2017-0002
|View full text |Cite
|
Sign up to set email alerts
|

Sarcomatoid Squamous Cell Carcinoma of the Penis – a Report of Two Cases

Abstract: Sarcomatoid squamous cell carcinoma of the penis is an uncommon tumor of this site with aggressive behavior and bad prognosis which might be related to the delay in medical examination and diagnosis. A correct and thorough morphological study is of great importance for the staging of the disease, treatment and follow up of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 9 publications
0
10
0
Order By: Relevance
“…Several cases of such lesions in the breast, larynx, vulva, penis, tibia, and other locations were reported. [2][3][4][5][6][7][8][9][10][11][12] Morphologically, all tumors in this review showed a population of poorly differentiated spindle tumor cells. No glandular structures were described.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Several cases of such lesions in the breast, larynx, vulva, penis, tibia, and other locations were reported. [2][3][4][5][6][7][8][9][10][11][12] Morphologically, all tumors in this review showed a population of poorly differentiated spindle tumor cells. No glandular structures were described.…”
Section: Discussionmentioning
confidence: 81%
“…We identified 10 articles describing 19 cases published from August 1981 to June 2022. [2][3][4][5][6][7][8][9][10][11] Collected significant data are presented in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously reported cases have also presented as friable, pedunculated masses with notable spindlecell morphology [1]. Two separate cases of elderly men in India and Japan presented with metastases to the lungs and stomach, respectively, and resulted in death within 6 months [5,6].…”
Section: Case Discussionmentioning
confidence: 99%
“…Sarcomatoid carcinomas are rare, aggressive biphasic tumors that can occur anywhere on the body, rarely involving the genitourinary system, particularly the penis [1]. Typically, this entity represents one to two percent of all penile carcinomas and is considered a variant of squamous cell carcinoma (SCC).…”
Section: Introductionmentioning
confidence: 99%